THE EFFECT OF HAND-TO-HAND EXCHANGE TRAINING ON DEVELOPING BACKHAND ACCURACY AMONG JUNIOR TABLE TENNIS PLAYERS - Hamdullah Abed Hammadi (Proximus Journal Publishing, 2025)
The study aims to identify the effect of using reciprocal training on developing backhand accuracy among junior table tennis players. The importance of this study stems from the need to develop the skill performance of junior players, especially in the formative stages, as the backhand is considered one of the most important basic skills in table tennis. The researcher used the experimental method due to its suitability for the nature of the study. The sample included (20) junior players aged (12-14) years, who were randomly selected from a club in Baghdad Governorate. The sample was divided into two equal groups: an experimental group that underwent an eight-week training program based on reciprocal training, and a control group that trained using the traditional method. A special test was used to measure backhand accuracy before and after the program was implemented, and statistical methods were used to analyze the results. The results showed statistically significant differences in favor of the experimental group, indicating the effectiveness of reciprocal training in developing backhand performance. These results provide practical evidence for coaches and those involved in youth training. They call for a review of traditional training programs and the introduction of diverse training techniques based on hand-to-hand exchanges, given their direct impact on developing technical skills. The study proposes expanding the scope of exchange training to include other skills and testing its impact on different age groups and levels.
Keywords: Exchange training; backhand; table tennis